Accuracy of dental models fabricated by CAD/CAM milling method and 3D printing method. - Wook-Tae Kim (Universidad de Concepción., 2018)
The purpose of this study was to evaluate the accuracy of a dental model fabricated using the CAD/CAM milling method and the 3D printing method. Materials and Method: This study was conducted in sequence of the digitization of the master model using an intraoral scanner, the manufacturing of working models (milling model, Multi-jet printing model and Color-jet printing model) by using the scan data of the master model, the digitization of the working model by using a laboratory scanner, the superimposition of the digital data of the master model and working models using inspection software, and 3-dimensional analysis. Ten measurements per group were done by one practitioner. One-way ANOVA and Tukey's post-hoc test were performed to compare the difference between the three groups. Results: The overall difference in models caused by the manufacturing method was measured as 73.05μm±9.64μm, 84.52μm±4.78μm, and 96.05μm±5.43μm in the milling group, Multi-jet printing group and Color-jet printing group, respectively. The difference according to the shape of the teeth, the abutment teeth among the three parts was recorded with the lowest values as 19.18±2.08μm, 77.10±7.48μm, and 56.63±4.58μm. Conclusions: Dental models manufactured by the CAD/CAM milling method presented superior accuracy over the models manufactured by the 3D printing method. Therefore, the use of optimized CAD software and appropriate materials is crucial for the fabrication accuracy of dental models.